Results of the Center for Disease Control Proficiency Testing Program for the detection of hepatitis B surface antigen. - Taylor, R N (1976)
The changes in the types and numbers of tests used by participants in the Center for Disease Control Proficiency Testing Program for the detection of hepatitis B surface antigen from the beginning of the program in 1971 until October 1975 are analyzed; the implications of these changes are discussed. Changes in the use of agar gel diffusion, rheophoresis, counterelectrophoresis, complement fixation, reverse passive latex agglutination, radioimmunoassay, and reverse passive hemagglutination tests are reviewed. The performance of the participants for 1975 is reported, and factors related to performance (type or combinations of tests used, procedures used to confirm specificity, etc.) are discussed. The increase in the use of third-generation tests in place of tests with lower sensitivity and the decrease in the use of multiple tests undoubtedly represent increased efficiency and effectiveness.